Hubungan Persepsi Tentang Peran Orang Tua Dengan Perilaku Seksual Remaja di SMP Kabupaten Pasaman - Dewi Susanti; Alsri Windra Doni; Lora Fazira (Jurnal Sehat Mandiri, 2021)
Parents as the first and foremost educators in the family have a very complex role. Lack of parental role can make adolescents fall into risky sexual behavior (RSB). RSB will have a negative impact on adolescents such as physical, psychological and social impacts. The purpose of this study was to examine the relationship between perceptions of the parents role and adolescent sexual behavior in the Pasaman District Junior High School. This type of research is an analytic survey with a cross sectional design. The study was carried out from January to March 2020 at 36 schools spread across 12 sub-districts taken by stratifield random sampling of 324 students. The instrument uses a standardized questionnaire that is valid and reliable. Data analysis with chi square with 95% confidence interval and p value < 0.05. In the study, it was found that the RSB of adolescents was 58,44% and the negative perception of the parents role was 53,2%. There is a relationship between perceptions of the parents role with RSB in adolescents (p value 0.001). Adolescents who have a negative perception of the parents role tend to have risky sexual behavior. It is recommended to the BKKBN to improve the BKR program to provide educational materials that are tailored to the educational level of parents. Creating a family empowerment program by integrating sexual education in the family